Joint design and simulation of GOX-GCH4 combustion and cooling in an experimental water-cooled subscale rocket engine - MEREU, Alexandru; ISVORANU, Dragos (INCAS bulletin, 2023)
This paper presents the authors’ most recent research regarding the feasibility of cooling a 1 kN scaled-down experimental rocket engine, running on gaseous oxygen and gaseous methane, for a ground test. The cooling segment of a rocket engine has always been a delicate problem, increasing the development time and costs of development. Since a series of problems can occur during the first ignition of a rocket engine prototype, removing as many potential issues from the initial test, such as using liquid methane for the cooling system, could result in a more stable experiment. Using water as the cooling agent can contribute to a more accelerated TRL increase of the engine’s subcomponents while reducing the risks taken for a whole assembly test. Thus, the combustion chamber, nozzle, and injector can be tested separately from the final cooling method, which can be added subsequently. In the present work, both a steady and transient CFD combustion simulation of a multicomponent compound, consisting of gaseous oxygen and gaseous methane was conducted in the combustion chamber of a small-scale rocket engine. The simulation is based on PDF-flamelet approach for the oxygen and methane combustion, along with real gas equations for the cooling agent.